THE INTERACTION OF FLOODS WITH TRANSPORT INFRASTRUCTURE - Ivan Vaníček; Jiří Vaníček (Acta Polytechnica CTU Proceedings)
Current demands on transport infrastructure are very often associated with the terms of “sustainability, availability and affordability”. The first term directly refers to the basic principles of sustainable construction in transport infrastructure, primarily motorway and railways, and how they are related to a very significant consumption of land, energy and natural aggregates. This paper is focused on the other two terms, availability and affordability. These principles are intended to guarantee proper functioning of communication even in nonstandard situations such as natural hazards, most typically floods. To avoid a total collapse of transport infrastructure, the term robustness is often applied, recognizing that this term is not a substitute for another outcome – namely a more expensive structure. The paper shows the possibilities for elimination of the negative impact of floods on transport infrastructure as they relate to different types of interaction and different types of floods.